Allelopathic effect of Lantana camara aqueous leaf extract on the seedling germination of Zea mays (maize) (Asian Journal of Agriculture, 2023)
Abstract. Mistica DJP, Magsino NJS, Tanjusay ZC, Paclibar GCB. 2023. Allelopathic effect of Lantana camara aqueous leaf extract on the seedling germination of Zea mays (maize). Asian J Agric 7: 83-87. Lantana camara L. is an invasive weed rampant in the Philippines and threatens agricultural crops. This study was conducted to evaluate the growth inhibitory effects of L. camara aqueous leaf extract in seedling germination of Zea mays L. Different concentration levels (25%, 50%, 75%, and 100%) of the L. camara leaf extracts as compared to the control were administered to the hypochlorite-treated seeds for two weeks. Results showed a significant difference among the treatments in the number of germinated seeds and main shoot and primary root elongation using ANOVA. Furthermore, the t-test revealed that the presence and absence of the aqueous leaf extract in seed germination are significantly different, showing significant inhibitory effects in the number of germinated seeds and the length of the shoot and root when the aqueous leaf extract was present. Moreover, in vitro assay also indicated that the concentration of the aqueous leaf extract is directly proportional to the growth inhibitory effects on seed germination and root and shoot elongation. Therefore, it is recommended to test the allelopathic effect of L. camara aqueous leaf extract in other agricultural crops and its effect on the soil and crop nutrition.
Keywords: Growth inhibitory effect, invasive weed species, Lantana bioassay, maize, root and shoot elongation